2021
DOI: 10.5334/joc.160
|View full text |Cite
|
Sign up to set email alerts
|

Single Word Reading in the “Real” World: Effects of Transposed-Letters

Abstract: We investigated single word reading in a context where isolated word presentation is not unusual -reading road signs in a simulated car driving situation. Participants had to indicate if the inscription on the road sign was a real word or not (lexical decision). The critical nonwords were created in two ways: by transposing two letters in a real word (e.g., the word "Highway" becomes "Hihgway") or by substituting the same two letters with different letters ("Hifpway"). The baseword used to create the critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Despite regular exposure to brand names daily, our ability to accurately identify counterfeit versions is relatively poor when we are incidentally exposed to them, making it challenging to distinguish between genuine and fake brand logotypes. The present ndings, using a novel VR setting during word recognition (see also 55 , for recent recent word recognition research using VR) showed that the di culty in accurately encoding and recognizing the detailed characteristics of complex logotypes, including their orthographic representations, extends to genuine and counterfeit versions. Finally, the present study builds on prior research demonstrating our poor orthographic processing and visual memory for common objects in naturalistic environments 21,22,56 .…”
Section: Discussionmentioning
confidence: 51%
“…Despite regular exposure to brand names daily, our ability to accurately identify counterfeit versions is relatively poor when we are incidentally exposed to them, making it challenging to distinguish between genuine and fake brand logotypes. The present ndings, using a novel VR setting during word recognition (see also 55 , for recent recent word recognition research using VR) showed that the di culty in accurately encoding and recognizing the detailed characteristics of complex logotypes, including their orthographic representations, extends to genuine and counterfeit versions. Finally, the present study builds on prior research demonstrating our poor orthographic processing and visual memory for common objects in naturalistic environments 21,22,56 .…”
Section: Discussionmentioning
confidence: 51%
“…The advent and easier accessibility of Virtual Reality (VR) technology have opened up new avenues for researchers, demonstrating the feasibility and viability of utilizing VR in experimental psychology as a transitional tool from 2D experimentation to a 3D immersive one 68,69 . The present findings, using a novel VR setting during word recognition (see 70 , for recent word recognition research using VR), showed that the difficulty in accurately encoding and recognizing the detailed characteristics of complex logotypes, including their orthographic representations, extends to genuine and counterfeit versions. Despite regular exposure to brand names daily, our ability to accurately identify counterfeit versions is relatively poor when we are incidentally exposed to them, thus making it challenging to distinguish between genuine and fake brand logotypes.…”
Section: Discussionmentioning
confidence: 51%
“…We selected 180 Spanish 5-letter non-diacritical words [e.g., amigo (friend)] from the EsPal database ( Duchon et al, 2013 ) with a mean Zipf frequency of 4.33 (range: 2.87–5.42). We created 180 nonwords by transposing the second and fourth letters of each base words (e.g., agimo), thus creating nonword stimuli that resembled words (see Perea et al, 2008b ; see also Mirault and Grainger, 2021 ; Perea et al, 2023b , for recent evidence of transposed-letter effects). None of the items had repeated or diacritical letters.…”
Section: Methodsmentioning
confidence: 99%